Combining Ability Analysis for Grain Yield and Yield Components using Potential Restorers in Pearl Millet: Combining ability in pearl millet restorers - BHARATH KUMARA K; B. K. Athoni; C. D. SOREGAON (Annals of Arid Zone, 2023)
Three A1 CMS sources (ICMB 94555, ICMB 98222 and ICMB 96666) were crossed with fifteen potential restorer lines in line × tester fashion to elucidate the information on the combining ability for seed yield and its component traits. A total of forty five crosses were evaluated for eleven different quantitative traits. Among the three lines used in the study, ICMB 96666 and ICMB 98222 exhibited significant gca effects for most of the characters studied and were found to be the good combiners. Likewise, among testers PRLN 117 and PRLN 109 were found to be good general combiners for most of the traits under observation. The estimates of variance components revealed predominance of non-additive gene action for most of the characters studied.